Improved control strategy for photovoltaic emulator using resistance comparison method and binary search method. (1st September 2017) - Ayop, Razman; Tan, Chee Wei
Highlights: Improved the operating point computational time up to 26 times. Reduced the operating point error up to 21 times. A robust control strategy with a fast and stable output. Abstract: The current Resistance Comparison Method uses a fixed-step size in the iteration process to determine the operating point of the photovoltaic emulator. The weakness of the fixed-step size is the inaccuracy of the produced operating point and that it requires a high number of iterations to converge, which can burden the controller processor. This paper proposed a Resistance Comparison Method with an adaptable step size using the Binary Search Method for the photovoltaic emulator. The advantages of this control strategy are the fast operating point tracking capability, highly accurate operating point, and no readjustment is needed for the controller of the closed-loop converter system (robust). The simulation of the photovoltaic emulator system is conducted in the MATLAB/Simulink® using current-mode controlled buck converter with a Proportional-Integral compensator and a single diode photovoltaic model with a series resistor. The results obtained are compared to the conventional control strategy of the photovoltaic emulator. The proposed control strategy demonstrates an average of iteration convergence of 26 times better and 21 times more accurate compared to the conventional Resistance Comparison Method.